Upgrading a manufactured fine aggregate for use in concrete using dry rare-earth magnetic separation. (November 2019) - André, Flávio P.; Miceli, Hayla; Moura, Luanna C.; Neumann, Reiner; Tavares, Luís Marcelo
Graphical abstract: Highlights: Dry magnetic concentration successful in upgrading manufactured fine aggregate. Concentration of unclassified feed rejected deleterious minerals and removed fines. Moisture content tolerable up to 0.5%, but other variables needed to be changed. Magnetic product with fine sizes and irregular shapes. Same concrete strength at 28 days with manufactured aggregate and natural sand. Abstract: Manufactured fine aggregates are progressively more used worldwide as an alternative to natural sand in concrete. In a recent study by the authors the removal of contaminants from manufactured fine gneiss aggregates by dry rare-earth magnetic separation was investigated. The present work initially demonstrates that single-stage dry high-intensity magnetic separation of the unclassified fine fraction (−2.36 mm) of the aggregate produced by a vertical shaft impact crusher allows simultaneous partial removal of the flaky biotite particles as well as reduction in the proportion of fines, thus improving its potential for application as a replacement of natural sand in concrete. The work then investigates the effect of magnetic field intensity, specific throughput, roll velocity, splitter position and moisture content on the performance of a bench-scale separator following a full factorial design of experiments. The non-magnetic product from an additional test was then used in combination with the coarser (+2.36 mm) unconcentrated fraction produced by a vertical shaft impact crusher in tests in concrete. Concretes with different strengths were prepared and results show that the upgraded non-magnetic manufactured aggregate was able to match the performance of concrete using natural sand, demanding one third less rheology additive, with comparable strengths at 28 days of curing.